Investigations into the Significance of the Evolutionary Descent of Prion Genes from Ancestral Zip Transporter - Salehzadeh, Ashkan (2012)
The conformational conversion of the cellular prion protein (PrPC) to PrP scrapie (PrPSc) is a hallmark of prion diseases [1]. The cellular role of PrP and the mechanism of PrPSc neurotoxicity remain largely elusive. Therefore, the identification of new prion-like proteins can assist in revealing the function of PrP. A recent study identified a sub-branch of ZIP (Zrt-, Irt-like protein) metal transporters, including ZIP5, ZIP6 and ZIP10, to be evolutionarily related to PrP. This thesis attempts to understand the functional relevance of this relationship between PrP and ZIP transporters with regard to PrP pathobiology. Preliminary observations indicated that PrP, ZIP6 and ZIP10 underwent endoproteolysis in scrapie-infected mouse brains. PrP and ZIP10 processing mimicked the proteolysis which occurs in cell culture during zinc-deficient conditions, suggesting that scrapie infection may be associated with zinc deficiency. More work is needed to uncover whether ZIPs can contribute to the propagation of prion diseases.